EXPLORING LIBRARY ANXIETY AMONG SUDANESE UNIVERSITY STUDENTS - K. A., Abusin; A.N., Zainab (Malaysian Journal of Library and Information Science, 2010)
Library anxiety is one of the psychological barriers that encounter students when they are performing a library task. This study explores library anxiety among 51 Sudanese university students using diary method for data collection. The finding indicates that library anxiety among Sudanese university students are manifested into five dimensions, namely; (a) Negative perceptions towards library environment, (b) Negative perceptions towards peer students, (c) Negative perceptions towards library staff, (d) Negative perceptions towards library services, and (e) Psychological barriers. Details of statements under the dimensions highlight the issues that are unique and not covered by previous studies in library anxiety.